Pengendalian Persediaan Bahan Baku Guna Mengoptimalkan Penyimpanan pada Gudang - Hardianto, Kresna Frantiarno; Purnama, Jaka (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The rapid development in the industrial world forces industry players to be required to pay attention to all aspects of business in their efforts to survive in competition, including control of raw material storage for the smooth production process. UD. XYZ is an industry engaged in the production of shovels, which in the production process involves several raw materials on a fairly large scale. The limited raw material storage space available results in frequent accumulation of some raw materials which can have an effect on the continuity of the production process. Calculations are carried out using the ABC classification method, inventory turnover ratio, and min-max stock on raw material control to avoid the accumulation of raw materials in the storage room. It was noted that there were several raw materials that experienced accumulation such as iron plates, iron pipes, screws and welding wires.